SNPs and human genetic variation (Henry Stewart Talks, 2025)
SNPs definition and significance, SNPs as markers for diversity and disease, SNP detection and analysis methods, GWAS, polygenic risk, pharmacogenomics, SNPs in population history and genetics, Large-scale sequencing and genetic variation, SNPs in personalized medicine